2015
DOI: 10.1186/s12936-015-0689-0
|View full text |Cite
|
Sign up to set email alerts
|

Re-imagining malaria: heterogeneity of human and mosquito behaviour in relation to residual malaria transmission in Cambodia

Abstract: BackgroundIn certain regions in Southeast Asia, where malaria is reduced to forested regions populated by ethnic minorities dependent on slash-and-burn agriculture, malaria vector populations have developed a propensity to feed early and outdoors, limiting the effectiveness of long-lasting insecticide-treated nets (LLIN) and indoor residual spraying (IRS). The interplay between heterogeneous human, as well as mosquito behaviour, radically challenges malaria control in such residual transmission contexts. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(108 citation statements)
references
References 24 publications
2
106
0
Order By: Relevance
“…Age or gender-specific behaviour (e.g., evening activities, division of household chores) or other social or cultural determinants including location and quality of houses may result in different levels of exposure. Such factors have been well investigated in settings in which most of the transmission is limited to specific population groups (e.g., in Southeast Asia [21][22][23]). In highly diverse settings such as PNG, one challenge will be to identify risk factors that disproportionately affect particular population groups, and to translate such knowledge into targeted control action.…”
Section: Discussionmentioning
confidence: 99%
“…Age or gender-specific behaviour (e.g., evening activities, division of household chores) or other social or cultural determinants including location and quality of houses may result in different levels of exposure. Such factors have been well investigated in settings in which most of the transmission is limited to specific population groups (e.g., in Southeast Asia [21][22][23]). In highly diverse settings such as PNG, one challenge will be to identify risk factors that disproportionately affect particular population groups, and to translate such knowledge into targeted control action.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Cambodia reported that respondents preferred soft, colorful market nets with small mesh over coarse, small, LLINs with larger mesh [36]. These findings were echoed in a willingness-to-pay study in Laos [37] and in Madagascar [38].…”
Section: Methodsmentioning
confidence: 99%
“…These data demonstrate how the malaria epidemiology can vary according to the ecological environment, the distribution of the vectors species, and human behavior, especially in unstable transmission areas. [22][23][24][25] This trend may be explained partly by the intense efforts at malaria control in Domain 2, where prompt malaria treatment is achieved through the widespread use of malaria RDTs and artemisinin-combined therapies in health facilities and at community level coupled with the increased coverage of LLITNs and indoor residual spraying that have led to a substantial fall in malaria transmission. This may have led to a slowing of the development of malaria immunity in adults who are still at a high risk of contracting malaria because of their work in the forests.…”
Section: Resultsmentioning
confidence: 99%
“…Strategies to protect high-risk individuals from contracting malaria need to be developed, taking into account that the two main forest-related vectors, Anopheles dirus and Anopheles minumus are outdoor biting mosquitoes. 22,32 Surprisingly, the PCR failed to detect 18 infections (0.23%) found positive by microscopy (five P. falciparum, 12 P. vivax, and one mixed P. falciparum/P. vivax).…”
Section: 29mentioning
confidence: 99%